Ethnocultural long-term care homes in Canada: a place for cultural inheritance and community building. (28th February 2023) - Niki, Izumi
Abstract : This article discusses the overlooked role of recreation programmes in the ethnocultural and cultural-specific long-term care home from my standpoint as a recreation worker. First, the policy during the pandemic that prohibited visits by family members and volunteers revealed that they are important informal caregivers to fill in for the limitations of workers. Second, recreational programmes can also be considered as a practice of cultural inheritance: staff and volunteers learn their history and reconstruct them as collective memory. Third, the interaction between residents, volunteers, families and workers generates a sense of belonging to the ethnic community. Therefore, it can be considered a practice of community building for minority ethnic groups. By presenting the significant role of recreation workers in a long-term care home, I aim to question the meaning and value of care work in long-term care facilities.